Hypoglycemic Effect of Lesser Yam (DioscoreahispidaDennst) Extract on Hyperglycemic Rats in Postprandial Condition - Ari Yuniastuti; Retno Sri Iswari; R Susanti; Yanuarita Tursinawati (Journal of Pharmaceutical and Health Research, 2021)
Hyperglycemia is a condition when the blood glucose levels exceed normal levels. Hyperglycemia can lead to the occurrence of Diabetes Mellitus (DM). The use of natural ingridients in lowering blood glucose levels has been carried out. However, studies on the benefits of lesser yam (Dioscorea esculenta) in reducing blood glucose levels have never been reported. This research aims to analyze the effect of administration lesser yam extract to hyperglycemic rats. Data were collected using experimental laboratoris pre-post test randomized design. Data were analysed using analysis of variance one way statistical test and advanced Tukey. Lesser yam contains Inulin as PLA (Water Soluble Polysaccharide) which serves to inhibit gastric emptying thus it can help manage a diet of people with hyperglycemic. The results obtained by the control group (not given treatment) shows no change in fasting blood glucose levels intesting as well as post prandial. The administration of lesser yam extract affects blood glucose levels to decreased in hyperglycemic rats in all groups. Significant decrease occurs in the testing conditions of first, second and third day post prandial group. The decrease is caused by the influence of the extracts after 2 hours of administration. Lesser yam (DioscoreahispidaDennst) is capable of lowering blood glucose levels of hyperglycemic rats in post prandial condition.